2021
DOI: 10.3389/fbioe.2021.642502
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mesenchymal Stem Cells Promote Extracellular Matrix Remodeling of Degenerated Nucleus Pulposus Cells via the miR-101-3p/EIF4G2 Axis

Abstract: The etiology of lumbocrural pain is tightly concerned with intervertebral disk degeneration (IDD). Bone mesenchymal stem cell (BMSC)-based therapy bears potentials for IDD treatment. The properties of microRNA (miRNA)-modified BMSCs may be altered. This study investigated the role and mechanism of BMSCs promoting extracellular matrix (ECM) remodeling of degenerated nucleus pulposus cells (NPCs) via the miR-101-3p/EIF4G2 axis. NPCs were collected from patients with IDD and lumbar vertebral fracture (LVF). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Yi et al used human tissue inhibitor of metalloproteinase 1 (TIMP-1) overexpression modified BMSCs to treat degenerated discs by directly targeting the ECM anabolic catabolic homeostasis [111]. In addition, Wang et al found that BMSCs promoted ECM regeneration in degenerated NP cells via the miR-101-3p/EIF4G2 axis [130]. However, stem cell injections or transplants alone often fail to achieve the desired effect due to their lack of protection and support by the ECM.…”
Section: Stem Cells Therapymentioning
confidence: 99%
“…Yi et al used human tissue inhibitor of metalloproteinase 1 (TIMP-1) overexpression modified BMSCs to treat degenerated discs by directly targeting the ECM anabolic catabolic homeostasis [111]. In addition, Wang et al found that BMSCs promoted ECM regeneration in degenerated NP cells via the miR-101-3p/EIF4G2 axis [130]. However, stem cell injections or transplants alone often fail to achieve the desired effect due to their lack of protection and support by the ECM.…”
Section: Stem Cells Therapymentioning
confidence: 99%
“…Wang et al found that MSCs could improve disk degeneration by promoting the remodeling of the extracellular matrix in the nucleus pulposus tissue. 34 Centeno et al found that transplantation of autologous MSCs into patients with disk degeneration caused a significant improvement in the prolapse of the nucleus pulposus tissue, and a significant reduction in pain. 35 However, stem cell transplantation techniques still have several limitations.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The ability of BMSCs to differentiate into chondrocytes was verified by differentiation experiments. Wang et al found that MSCs could improve disk degeneration by promoting the remodeling of the extracellular matrix in the nucleus pulposus tissue . Centeno et al found that transplantation of autologous MSCs into patients with disk degeneration caused a significant improvement in the prolapse of the nucleus pulposus tissue, and a significant reduction in pain …”
Section: Discussionmentioning
confidence: 99%
“…EIF4G2 is related to the alternative scanning of the translation start site by the 40S ribosomal subunit, translation associated with alternative ORFs, and translation under stress [ 51 , 52 ]. EIF4G2 differential expression was previously related to extracellular matrix remodeling [ 53 ]. However, most of the literature regarding this gene explores its interaction with microRNAs, and no metformin effect on EIF4G2 expression has been previously reported.…”
Section: Resultsmentioning
confidence: 99%